Линейные уравнения
- \(2x=4\)
- \(3x=-9\)
- \(-4x=8\)
- \(3x=7\)
- \(3(x+1)-4(x-2)=9\)
- \(4(x-1)+2(3-x)=7x\)
- \(x+2x+3x=1+2+3\)
- \(x+2(x+3(x+4))=8\)
- \(x+3=x+2\)
- \(2(x+2)=2(x+3)\)
- \(2015+x=x+2015\)
- \(\displaystyle\frac{x}{2}=\frac{1}{6}\)
- \(\displaystyle\frac{x+1}{2}=\frac{x-1}{5}\)
- \(\displaystyle\frac{x}{3}-\frac{x}{4}=\frac{1}{6}\)
- \(\displaystyle\frac{2x-3}{15}+\frac{1-x}{9}=\frac{2-x}{6}-1\)
- \((x+1)(x+2)=(x-1)(x-100)\)
- \(2015(x-1)+x^2=x(2016+x)+2015\)
- \(2(x-(x-(x-(x-10))))=3(1-(1-(1-x)))\)
- \(\displaystyle\frac{50}{x}=\frac{2}{9}\)
- \(\displaystyle\frac{4}{x-1}=\frac{3}{x+3}\)
- \(0,5+2x=1,5+3x\)
- \(\displaystyle\frac{3}{5}x-\frac{x}{2}=0,2\)
- \(\displaystyle\frac{17}{5x}=2-\frac{7}{x}\)
- \((x+2)^2-5(x-4)=(x-6)(x+6)\)
- \(\displaystyle\frac{17x+26}{4x+3}-3=0\)
- \(6-\displaystyle\frac{x-1}{2}=\frac{3-x}{2}+\frac{x-2}{3}\)
- \(\displaystyle\frac{2}{3}(x+3)=\frac{6+2x}{3}\)
- \(0,2(x-1)+0,5(3x-9)=\displaystyle\frac{x}{3}-2\)
- \(3(-0,5+2x^2-(x+2)(2x-4))=-20+5x\)
- \(\displaystyle\frac{x}{2}+\frac{x}{12}+\frac{x}{42}=-6-\frac{x}{30}-\frac{x}{20}\)
- \(7-2(x-3(x-3(x-3)))=2\)
- \((x-3)^2-x(x+4)=15-10x\)
- \(\displaystyle\frac{8}{9}x+\frac{34}{72}-\frac{9}{8}x=0\)
- \(\displaystyle\frac{4+x}{4x-2}+\frac{3}{4}=0\)
- \(\displaystyle\frac{5}{x}+\frac{1}{x^2}=0\)
- \(\displaystyle\frac{3}{2-\frac{3}{2-x}}=\frac{21}{8}\)